Fatigue strength of HVOF sprayed Cr(3)C(2)-25NiCr and WC-10Ni on AISI 4340 steel - Souza, R. C.; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, M. O. H. [UNESP] (Elsevier B.V. Sa, 2008)
The fatigue strength of coated material is significantly influenced by internal residual stresses. Chromium coatings are used in applications to guarantee protection against wear and corrosion, combined with chemical resistance and good lubricity. The reduction in the fatigue strength of base material and since this technology presents detrimental environmental and health effects. resulted in the search on coatings viewed as being capable of replacing hard chrome plating.Thermally sprayed HVOF coatings are being considered to replace galvanic chromium deposits in industrial applications with, at least, comparable performance with respect to wear and corrosion resistance. The aim of the present study is to compare the influence of Cr(3)C(2)-25NiCr and WC-10Ni coatings applied by HVOF process and hard chromium electroplating on the fatigue strength, abrasive wear and corrosion resistance of AISI 4340 steel. S-N curves were obtained in axial fatigue tests for base material, chromium plated and HVOF coated specimens.Experimental data showed higher axial fatigue resistance for HVOF coated specimens in comparison to electroplated chromium. The wear weight loss tests indicated better results for the HVOF thermal spray processing in comparison to the chromium electroplating. An increase in the corrosion resistance of steel protected with WC-10Ni HVOF coatings occurred with increased coating thickness. For Cr(3)C(2)-25NiCr HVOF coating, results indicate clearly the higher salt spray resistance. (C) 2008 Published by Elsevier B.V.
Keywords: Thermal spray coatings; Fatigue; Wear; Corrosion; AISI 4340 steel